Isolation and Identification of Flavonoids from Mundu Plant Leaves (Garcinia Dulcis (Roxb.) Kurz) - Hutagalung, Natalia; Sembiring, Helmina Br. (Journal of Chemical Natural Resources, 2022)
Isolation and identification of the flavonoid compounds found in the leaves of the mundu plant (Garcinia dulcis (Roxb.) Kurz) have been carried out. The leaves of the mundu plant were extracted by maceration with methanol solvent. The concentrated methanol extract was added to distilled water and then filtered. Aquadest filtrate partitioned with ethyl acetate. Concentrated ethyl acetate extract was dissolved with methanol and partitioned with n-hexane solvent. The concentrated methanol extract was analyzed by thin layer chromatography and separated by column chromatography with chloroform as eluent: methanol (90:10) v/v ; (80;20) v/v ; (70:30) v/v ; (60:40) v/v. The compounds obtained were purified by preparative thin layer chromatography, producing a yellow amorphous solid of 8.4 mg with a value of Rf = 0.35 using chloroform: ethyl acetate (40:60) v/v as the eluent. The compounds obtained were analyzed using UV-Visible Spectrophotometer, Infrared Spectrophotometer (FT-IR), and Proton Nuclear Magnetic Resonance Spectrophotometer ( 1H-NMR). Based on the analysis and interpretation of spectroscopic data, it is suspected that the isolated compounds obtained are flavonoid compounds, namely the biflavonoid group.